A justiça em Aristóteles e a mediação extrajudicial de conflitos - Stefanoni, Luciana Renata Rondina (2018)
The concepts related to Justice in Aristotle influenced the law of several legal systems, especially those influenced by Roman legal paradigms. Ethics in Aristotle was decisive in the construction of those. The mediation of conflicts incorporates much of the Greco-Roman ideology about Justice. Nowadays, with the jurisdictional crisis, mediation has come to occupy a prominent place among the methods of conflict resolution, so that it has reached a "point of mutation", becoming an indispensable institute for social peace and harmony. The objective of this work is to establish a relation between the theory of Justice in Aristotle and the institute of mediation in the context of the civil process, as applied today in Brazil. The thesis that is defended is that mediation is capable of reaching Justice in the Aristotelian sense, more effectively than Jurisdiction, because it is closer the origins of the theory than the civil procedural law. For that, we proceeded to the bibliographical research, in the historical, philosophical, legal-philosophical and juridical-procedural references pertinent to the species. Regarding the exposition, the deductive method was used, in order to have started from the amplitude of the concepts of Aristotelian justice to the specificities of the institute of mediation. We conclude that, in fact, mediation is an instrument capable of reaching justice in the sense desired by Aristotle